Enhanced toxicity and antifungal effects of iron-oxide chitosan/samarium/ranitidine microparticles - Kusrini, Eny; Nuzula, Khairu; Anwar Usman,; Wilson, Lee D.; Gunawan, Cindy; Prasetyo, Agus Budi (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study aimed to investigate the cytotoxicity and antifungal properties of Sm(NO3)3.6H2O salt, chitosan/Sm complex, iron oxide (Fe3O4 NPs), and iron-oxide modified chitosan/Sm/ranitidine microparticles. The microparticles of iron-oxide modified chitosan/Sm/ranitidine composites were synthesized from various masses of Sm(NO3)3.6H2O (250-350 mg), chitosan (2,000-2,500 mg), and (5-25 mg) through the microwave-assisted evaporation method. The Fe3O4 NPs and ranitidine/Sm were mixed with chitosan through a dispersion method by microwave. The toxicity studies of iron-oxide modified chitosan/Sm/ranitidine composites showed 50% lethal concentration in the range from 3,600 to 3,900 μg/mL on the aquatic crustacean Artemia salina, suggesting their slight toxicity. Antifungal activities for all samples were determined using the agar diffusion and serial dilution methods. The iron-oxide modified chitosan/Sm/ranitidine composites showed inhibition zone diameter of Aspergillus niger from 18.33 to 14.67 mm at 1,000 μg/mL. All composites and chitosan/Sm complex showed bioactivity properties with minimum inhibitory concentration values of 2.5 μg/mL against A. niger. These composites and chitosan/Sm complex have the same minimum fungicidal concentration, showing the potential to inhibit fungi. Overall results suggested that modifying the structure of chitosan using Sm3+, Fe3O4 NPs, and ranitidine enhanced its physical, chemical, and biological properties as an antifungal agent.